2022
DOI: 10.1177/26334895221096293
|View full text |Cite
|
Sign up to set email alerts
|

Refining an implementation strategy to enhance the reach of HIV-prevention and behavioral health treatments to Latino men who have sex with men

Abstract: Background: Latino men who have sex with men (LMSM) experience HIV and behavioral health disparities. Yet, evidence-based interventions, such as pre-exposure prophylaxis (PrEP) and behavioral health treatments, have not been equitably scaled up to meet LMSM needs. To address quality of life and the public health importance of HIV prevention, implementation strategies to equitably scale-up these interventions to LMSM need to be developed. This study identifies themes for developing culturally grounded implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Ultimately, the collaborative redesign process allowed greater alignment with HELM components and school needs and priorities and should, in theory, increase adoption and implementation. These findings are consistent with recent calls for more tailorable or customizable implementation in complex settings ( Munson et al, 2022 ) and other efforts to collaboratively redesign implementation strategies outside the education sector ( Deatrick et al, 2021 ; Harkness et al, 2022 ). Given there are a number of usability challenges for implementation strategies when applied to novel settings, it is critical to ensure redesign solutions address barriers in the implementation context ( Lyon et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Ultimately, the collaborative redesign process allowed greater alignment with HELM components and school needs and priorities and should, in theory, increase adoption and implementation. These findings are consistent with recent calls for more tailorable or customizable implementation in complex settings ( Munson et al, 2022 ) and other efforts to collaboratively redesign implementation strategies outside the education sector ( Deatrick et al, 2021 ; Harkness et al, 2022 ). Given there are a number of usability challenges for implementation strategies when applied to novel settings, it is critical to ensure redesign solutions address barriers in the implementation context ( Lyon et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…17,18 Provider cultural competence was also a key determinant for both measures and may relate to the stigma that LSMM encounter; it may be difficult for LSMM to find a PrEP/HIV testing provider who is a good fit for them because they may not be LGBTQ affirming and/or may not be knowledgeable about LSMM. 19 By administering the measure, stigma at the interpersonal-level and cultural competence at the structural-level may arise as factors deterring LSMM from obtaining PrEP services. As a response, a health promotion tactic may be to develop stigma reduction campaigns and/or cultural training.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior qualitative work, LSMM in South Florida noted that strategies to equitably scale up HIV prevention services should be available in multiple languages, most importantly, Spanish and English. 19 Additionally, LSMM’s immigration status should be considered with regard to engagement in HIV prevention services; research has shown that a fear of deportation had an indirect effect on reduced HIV testing among Latina/o/x individuals. 20 in practice, it may be useful in some settings for health promotion professionals to determine whether higher scores on this factor are driven more by language, immigration, or both when using the findings to inform their work.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, participants shared with interviewers that they appreciated the opportunity to share about their experiences during an acutely stressful period. Our rapid research has since laid the groundwork for subsequent research examining COVID-19 vaccine engagement among LSMM (Weinstein et al, 2022) and informed our development of an implementation strategy to facilitate LSMM’s uptake of HIV-prevention and behavioral health treatment (Harkness, Weinstein, Lozano et al, 2022).…”
Section: Case Examplesmentioning
confidence: 99%